POLITICAL MOVEMENT OF EQUALITY IN ACTION: A PHILOSOPHICAL ANALYSIS OF JACQUES RANCIÈRE'S THOUGHTS ACCORDING TO TODD MAY IN ITS RELEVANCE WITH CURRENT POLITICAL MOVEMENTS IN INDONESIA (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Abstract Todd May, as he summed up Rancière's thoughts on democracy, argues that what is meant by democracy is not about the form of a government or social order. Democracy is an act of political subjectivity that disrupts the social order by demos to verify equality. Demos political order always takes the form of disagreement (dissensus). The verification process of demos that disrupts the day-to-day political order (police) is what Todd May calls democratic politics. The demos action presupposes equality and starts on equality with the result of emancipation. The so-called demos are people who in the social order are considered to have no part, are not taken into account, such as blacks, women, indigenous people, workers, the poor, people in general who are considered and treated unequally in the social order dominant. Their presence in the social order is not identified. According to Rancière, with the democratic demos movement those who were not previously identified could be identified again. The act of verifying equality by demos is an effort to find the existence of equality within the police. The emergence of demos transforms the social order into different forms, which accommodate their countless existence (demos, the wrong) in the police.   Keywords:political movements, equality, democracy, demos